Alzheimer‐related protein APL‐1 modulates lifespan through heterochronic gene regulation in Caenorhabditis elegans. Issue 6 (24th August 2016) - Ewald, Collin Y.; Marfil, Vanessa; Li, Chris
Summary: Alzheimer's disease (AD) is an age‐associated disease. Mutations in the amyloid precursor protein (APP) may be causative or protective of AD. The presence of two functionally redundant APP ‐like genes (APLP1/2) has made it difficult to unravel the biological function of APP during aging. The nematode Caenorhabditis elegans contains a single APP family member, apl‐1 . Here, we assessed the function of APL‐1 on C. elegans' lifespan and found tissue‐specific effects on lifespan by overexpression of APL‐1. Overexpression of APL‐1 in neurons causes lifespan reduction, whereas overexpression of APL‐1 in the hypodermis causes lifespan extension by repressing the function of the heterochronic transcription factor LIN‐14 to preserve youthfulness. APL‐1 lifespan extension also requires signaling through the FOXO transcription factor DAF‐16, heat‐shock factor HSF‐1, and vitamin D‐like nuclear hormone receptor DAF‐12. We propose that reinforcing APL‐1 expression in the hypodermis preserves the regulation of heterochronic lin‐14 gene network to improve maintenance of somatic tissues via DAF‐16/FOXO and HSF‐1 to promote healthy aging. Our work reveals a mechanistic link of how a conserved APP‐related protein modulates aging.